Potret Pandangan Mahasiswa Mengenai Insan Pers - Awanis Akalili; Ayu Usada Rengkaningtias; Nabila Ikrima (Universitas Negeri Surabaya, 2026)
One of the pressing issues facing the Indonesian press is the lack of regeneration. Young people seem to have no interest in pursuing journalism as a profession. Yet, the sustainability of the press plays a vital role as a pillar of democracy in Indonesia. This issue underscores the importance of establishing a common understanding and fostering synergy through focus group discussions (FGDs). The purpose of this Focus Group Discussion (FGD) was to identify the root cause of the lack of interest among young people in the profession of journalism and to provide recommendations for solutions to the regeneration problem, ensuring continued interest in this profession for the success of the press in Indonesia. This PkM was held in the form of FGDs using a consultation method to foster synergy with universities. To this end, the Department of Communication Sciences, UNY, collaborated with a partner, the Alliance of Independent Journalists (AJI) Yogyakarta. This FGD was useful in addressing the problem of the younger generation's lack of interest in the profession of journalism. The FGD yielded several findings, indicating that prior to the FGD, students had misperceptions about the profession of journalists, including confusion about the concept of journalism, journalism products, and the perception that the profession of journalists is less promising in this era. To address this issue, several recommendations were made. 1) Academics need to adjust the curriculum; they must introduce the spirit of journalism to students, provide basic writing and reading skills, and provide students with relevant skills for the times. 2) Practitioners need to provide facilities and regulations for young journalists and offer alternative business models. 3) Students need to increase their capacity for collaborative projects and their interest in journalism. Even in the digital era, students need to realize the importance of developing writing and reading skills as the foundation of journalism. Keywords: The future of the press, The Glory of Indonesian press, regeneration of the Indonesian press